Block of voltage-dependent calcium channels by aliphatic monoamines. - Beedle, A M (2000)
We have recently identified farnesol, an intermediate in the mevalonate pathway, as a potent endogenous modulator and blocker of N-type calcium channels (Roullet, J. B., R. L. Spaetgens, T. Burlingame, and G. W. Zamponi. 1999. J. Biol. Chem. 274:25439-25446). Here, we investigate the action of structurally related compounds on various types of voltage-dependent Ca(2+) channels transiently expressed in human embryonic kidney cells. 1-Dodecanol, despite sharing the 12-carbon backbone and headgroup of farnesol, exhibited a significantly lower blocking affinity for N-type Ca(2+) channels. Among several additional 12-carbon compounds tested, dodecylamine (DDA) mediated the highest affinity inhibition of N-type channels, indicating that the functional headgroup is a critical determinant of blocking affinity. This inhibition was concentration-dependent and relatively non-discriminatory among N-, L-, P/Q-, and R-Ca(2+) channel subtypes. However, whereas L-type channels exhibited predominantly resting channel block, the non-L-type isoforms showed substantial rapid open channel block manifested by a speeding of the apparent time course of current decay and block of the inactivated state. Consistent with these findings, we observed significant frequency-dependence of block and dependence on external Ba(2+) concentration for N-type, but not L-type, channels. We also systematically investigated the drug structural requirements for N-type channel inhibition. Blocking affinity varied with carbon chain length and showed a clear maximum at C12 and C13, with shorter and longer molecules producing progressively weaker peak current block. Overall, our data indicate that aliphatic monoamines may constitute a novel class of potent inhibitors of voltage-dependent Ca(2+) channels, with block being governed by rigid structural requirements and channel-specific state dependencies.